1999
DOI: 10.1093/oxfordjournals.schbul.a033376
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clozapine, Risperidone, and Olanzapine on Cognitive Function in Schizophrenia

Abstract: Cognitive function is markedly impaired in most patients with schizophrenia. Antecedents of this impairment are evident in childhood. The cognitive disability is nearly fully developed at the first episode of psychosis in most patients. The contribution of cognitive impairment to outcome in schizophrenia, especially work function, has been established. Preliminary results indicate that cognitive function, along with disorganization symptoms, discriminate schizophrenia patients who are able to work full-time fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
550
6
8

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 920 publications
(588 citation statements)
references
References 97 publications
24
550
6
8
Order By: Relevance
“…It has been widely reported that atypical antipsychotics have some beneficial effect on cognitive deficits [9,23,24,40,50]. However, it is important to appreciate the limitations of models such as this one as, although clozapine and risperidone effectively reversed the cognitive deficits observed in this experiment, the CATIE study highlights the fact that these antipsychotics do not provide consistent improvement of cognitive symptoms in patients [38].…”
Section: Discussionmentioning
confidence: 80%
“…It has been widely reported that atypical antipsychotics have some beneficial effect on cognitive deficits [9,23,24,40,50]. However, it is important to appreciate the limitations of models such as this one as, although clozapine and risperidone effectively reversed the cognitive deficits observed in this experiment, the CATIE study highlights the fact that these antipsychotics do not provide consistent improvement of cognitive symptoms in patients [38].…”
Section: Discussionmentioning
confidence: 80%
“…Specifically, clozapine has demonstrated limited or no effects on executive function (Meltzer and McGurk, 1999;Hoff et al, 1996;Bellack et al, 2004). Risperidone has been shown either to be not effective (Bellack et al, 2004;Remillard et al, 2005;Lee et al, 2007) or slightly effective, as measured by Wisconsin Card Sorting Test (Meltzer and McGurk, 1999;Harvey et al, 2005), and olanzapine produces effects in the same range as risperidone (Meltzer and McGurk, 1999;Bilder et al, 2002;Keefe et al, 2007). In a small clinical trial, sertindole has shown superiority to haloperidol on executive function performance (Gallhofer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Novel antipsychotic compounds (second-generation or 'atypical' antipsychotics) such as clozapine (Fitton and Heel, 1990), olanzapine (Fulton and Goa, 1997), and sertindole (Kane and Tamminga, 1997;Azorin et al, 2006) have some beneficial effect on negative symptoms and reduced potential to produce extrapyramidal side effects, but these agents have demonstrated inconsistent effects on cognitive function in patients with schizophrenia. Depending on the type of cognitive domain measured, second-generation antipsychotics have been reported to produce improvement (Mortimer 1997;Meltzer and McGurk, 1999;Keefe et al, 2007), no effect (Hoff et al, 1996;Meltzer and McGurk, 1999), and impairment (Goldberg et al, 1993). The effect of sertindole on cognitive function has not been investigated extensively; however, a small clinical trial indicates a beneficial effect on some cognitive substrates, including executive function, in individuals diagnosed with schizophrenia (Gallhofer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…If similarities between schizotypy and schizophrenia existed on the neurochemical level, one would expect task performance to improve in schizotypal individuals with (second-generation) DA antagonists. Specifically, atypical neuroleptic agents were found to improve neuropsychological functioning including immediate recall, visuo-spatial construction, executive functions, verbal fluency, attention, and working memory (see eg Cuesta et al, 2001;Meltzer and McGurk, 1999;Purdon et al, 2001;Sumiyoshi et al, 2003 for overviews). However, our schizotypal participants performed in a most adaptive way after a DA agonist.…”
Section: Discussionmentioning
confidence: 99%